2020
DOI: 10.1177/0886260520906183
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Neighborhood Characteristics and Experiences of Intimate Partner Violence: A Multilevel Analysis

Abstract: Within a lifetime, one in four women and more than one in 10 men will experience intimate partner violence (IPV). Researchers have begun to examine physical and social neighborhood risk factors of IPV, often using cross-sectional data. Most studies focus on risk or promotive factors. Often, neighborhood factors are studied through the lens of social disorganization theory, which focuses on how a neighborhood slips into a violent and crime-ridden place. Busy streets theory provides an alternative perspective, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…A 24year longitudinal study also suggested that people perceived more positive neighborhoods as less likely places to experience IPV and individual experiences of violence are reinforced by the observing of neighborhood risk factors (e.g. alcohol or drug misuse, neighborhood violence observed) [76]. Negative views of human behaviors and conflict relationships can be fostered during pregnancy by a perception of threatening and dangerous environments that turn to feelings of isolation and powerlessness and trigger physiological responses (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A 24year longitudinal study also suggested that people perceived more positive neighborhoods as less likely places to experience IPV and individual experiences of violence are reinforced by the observing of neighborhood risk factors (e.g. alcohol or drug misuse, neighborhood violence observed) [76]. Negative views of human behaviors and conflict relationships can be fostered during pregnancy by a perception of threatening and dangerous environments that turn to feelings of isolation and powerlessness and trigger physiological responses (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A 24-year longitudinal study also suggested that people perceived more positive neighborhoods as less likely places to experience IPV and individual experiences of violence are reinforced by the observing of neighborhood risk factors (e.g. alcohol or drug misuse, neighborhood violence observed) [74]. Negative views of human behaviors and con ict relationships can be fostered during pregnancy by a perception of threatening and dangerous environments that turn to feelings of isolation and powerlessness and trigger physiological responses (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A 24-year longitudinal study also suggested that people perceived more positive neighborhoods as less likely places to experience IPV and individual experiences of violence are reinforced by the observing of neighborhood risk factors (e.g. alcohol or drug misuse, neighborhood violence observed) (Thulin et al, 2020). Negative views of human behaviors and conflict relationships can be fostered during pregnancy by a perception of threatening and dangerous environments that turn to feelings of isolation and powerlessness and trigger physiological responses (e.g.…”
Section: Discussionmentioning
confidence: 99%